PREDIKSI KEHADIRAN PESERTA RAKORNAS APTIKOM MENGGUNAKAN METODE LEAST SQUARE - Cristina Adelia Putri Silaban; Manalu, Darwis Robinson; Margaretha Yohanna (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2025)
APTIKOM (Asosiasi Pendidikan Tinggi Informatika dan Komputer) is an association that brings together Indonesian Universities offering Computer Science and Information Technology programs, playing a role in curriculum development, educational standards, and professional certification in the field of Information Technology (IT). Predicting the number of participants at the APTIKOM National Conference can provide an estimate of the number of participants for the following year, helping the conference organizing committee plan activities more effectively anda data-driven using the Least Square method. The prediction results are analyzed and categorized into activity levels based on participant attendance frequency. The model evaluation results indicate that the Least Square method can be effectively used to predict participation patterns and generate useful category analyses as a basis for decision-making by APTIKOM.